Anomalies of the external auditory canal in children (Herald of the National Children's Medical Center, 2024)
Abstract: The aim of the examination is to increase the effectiveness of auditory-speech rehabilitation of patients with malformations of the outer and middle ear in children by optimizing the diagnostic algorithm, developing and introducing new methods of surgical treatment of this pathology.Materials and methods of research: The study included 115 patients with congenital atresia of the external auditory canal.Results of the study: The patients were divided into 2 groups depending on the type of anomaly of the outer and middle ear, surgical technique, and further management tactics. Group I included 52 (45,2%) clinical cases aged from 5 to 17 years, which were diagnosed with stenosis of the membranous section or stenosis of the membranous section of the external auditory canal and atresia of the medial (bone) sections of the external auditory canal, normal or slightly hypoplastic tympanic cavity, deformed auditory ossicles and a well-ventilated mastoid process with various types of malformations of the external ear. Group II included 63 (54,8%) clinical cases of patients who had no external auditory canal, the middle ear was hypoplastically developed, the auditory ossicles were severely deformed, and inhibition of pneumatization of mastoid cells was also detected.Conclusion: The absence of relapses of congenital stenosis of the external auditory canal in 88.4% of cases in patients of group I in the long-term postoperative period indicates the effectiveness of the treatment methods used. In case of congenital stenosis and atresia of the medial sections of the external auditory canal, it is necessary to completely remove the upper part of the auditory canal, as well as expand the entrance of the auricle to the upper, posterior and lower sections. Complete transfer of the skin clot was assessed as the reason for the absence of re-formation of atresia, resulting in a stable anatomical result.In the long-term postoperative period, the absence of repeated narrowing of the external auditory canal, which occurred in 88.9% of patients in group II, indicates the effectiveness of the methods used. The fact that the diameter of the formed external auditory canal is at least 1 cm, that its bone wall is completely covered with a skin clot, that the lingual clot on the anterior wall is located freely, and that the distal part of the skin clot is tightly sutured to the skin was regarded as the reason for the absence of re-formation atresia, resulting in a stable anatomical result.In 13 cases, relapse of stenosis was caused by chronic skin diseases of patients, untimely consultation with a doctor, as well as constant moisture in the external auditory canal due to hair growth in the skin flap, the formation of the external auditory canal in the bony part by less than 1 cm and perichondritis of the auricle.
Keywords: malformation; auditory ossicles; congenital atresia of the external auditory canal